Piroxicam and doxycycline treatment for an oral squamous cell carcinoma in an inshore bottlenose dolphin (Tursiops aduncus). Issue 6 (11th May 2016) - March, DT; Blyde, DJ; Bossart, GD; Begg, AP; Taylor, DP; McClure, V
Abstract : Background: The virus family Papillomaviridae has been documented in a wide range of animal species and can cause benign and malignant proliferative lesions. The presence of concurrent lingual papillomas and squamous cell carcinomas (SCC) in cetaceans has also been documented in both wild and captive populations, suggesting malignant transformation of benign papilloma to SCC may occur in this species. Case report: In 2008, a 38‐year‐old captive male inshore bottlenose dolphin ( Tursiops aduncus ) was diagnosed with papillomatous lesions on the intermandibular frenulum rostral to the tongue and an infiltrative SCC of the soft palate following biopsy and histological analysis. A treatment regimen of piroxicam and doxycycline was initiated with misoprostol as a gastroprotectant. The treatment resulted in a marked reduction in tumour size and reversible hepatotoxicosis. Subsequent biopsies revealed the presence of SCC in the oral cavity; however, the disease remains stable at the time of writing. Conclusion: To the best of our knowledge, this case is the first report of piroxicam and doxycycline used to treat SCC in a bottlenose dolphin. The treatment was successful in reducing the clinical presentation of the disease.